The geography of international conservation interest in South American deforestation frontiers - Qin, Siyu (2022)
International funding is increasingly important in supporting conservation in mega-biodiverse countries. However, it remains unclear which donors invest in which conservation objectives and where, making it difficult to identify gaps and key actors to influence. Here we identified 1947 foreign-aided conservation projects in South America's major deforestation frontiers and summarized their objectives and interventions over time and space. We found that conserving nature for its own sake and for ecosystem services remained key objectives, but the types of interventions varied considerably over time. Geographically, international conservation prioritized moist forests over drier biomes, despite equally high deforestation risk. Different donor groups emphasized specific objectives and interventions that reflected socioecological links (e.g., bird migration, colonial history) between donating and receiving regions, as well as the donors’ values (e.g., iconic/endangered species, human rights). These telecoupled patterns provide both opportunities and barriers for conservation and have implications for conservation prioritization strategies.